Robots, artificial intelligence, and service automation in travel, tourism and hospitality - Ivanov, Stanislav; Webster, Craig (Emerald Publishing Limited, 2019)
Using a combination of theoretical discussion and real-world case studies, this book analyses the use of robotics, artificial intelligence and services automation (RAISA) within the travel, tourism and hospitality industries. Divided into two sections, the book first concentrates on the theoretical aspects surrounding the use of RAISA in travel, tourism and hospitality. Themes explored include: economic fundamentals customer attitudes chatbot adoption service quality Following on from this, the second section concentrates on current and future use of RAISA technologies in specific subsectors of the tourism economy: hotels, restaurants, travel agencies, museums, and events. With an international scope of authorship and focus, the book is a useful reference source for scholars, students, and general readers interested in robotics, artificial intelligence, and automation technologies. Alongside this, the business insights and case studies examined in the book offer practitioners guidance on how these technologies can and will be incorporated into organizations, particularly those in the travel and tourism industry.